The major contributions of Ibn Khaldun, Al Kindi and Ibn Rushd to the field of social sciences and humanities - Ashimi, Tijani Ahmad (Asian Scholars Network (ASNet), 2023)
The role of great Muslim scholars and Muslim Philosophers in the field of social sciences and humanities is very remarkable. Indeed, the history has recorded the excellent contributions of some energetic Muslim scholars to this field, such as Ibn-Khaldun, Al-Ghazali, Ibn Sina, Al-Farabi, al Bairuni etc. Hence, the objective of this article is to explore the immense contributions of these scholars with particular reference to the unique contributions of Ibn-Khaldun, Al-Kindi and Ibn Rushd. The article will also assess the impact of these Muslim scholars to modern human sciences. Yet, for the sake of academic writing, this article will apply the descriptive and analytical methods, that is by exploring and analyzing the works of these scholars .Finally, the article will provide a brief conclusion with some recommendations.